Atmospheric River Brings Warmth and Rainfall to the Northern Antarctic Peninsula During the Mid-Austral Winter of 2023 - Bozkurt, D.; Carrasco Cerda, Jorge Fernando; Cordero, R. R.; Fernandoy, F.; Gomez-Contreras, A.; Carrillo, B.; Guan, B. (My University, 2024)
Contrasting the extensive research on summer atmospheric rivers (ARs) in the Antarctic Peninsula (AP), winter AR impacts are less understood. This study examines a unique warming event from 1 to 3 July 2023, using in situ winter observations and ERA5 reanalysis. On 2 July, Frei station experienced an extreme warm event with a temperature of 2.7 degrees C and a significant rise in the freezing level, coinciding with winter rainfall. A pressure dipole pattern over the AP, with contrasting circulations over Bellingshausen and Weddell Seas, facilitated an AR, carrying warm, humid air initially from South America/Atlantic and then the southeast Pacific. This shift resulted in anomalous water stable isotope composition in precipitation. Trends suggest a strengthening winter pressure dipole, associated with increased AR frequency and higher temperatures in northern AP. These findings highlight the importance of winter observations in exploring AR impacts, bridging knowledge gaps about winter AR behaviors. The Antarctic Peninsula is increasingly witnessing climate extremes during summer, while the understanding of such extremes in winter remains limited. Our study explores a significant warming event in the northern Peninsula in early July 2023, utilizing recent winter in situ observations and atmospheric analysis. On 2 July, an exceptional temperature of 2.7 degrees C was recorded, significantly altering the atmospheric freezing level and causing rainfall instead of snow. Our analysis revealed a unique atmospheric pattern around the Peninsula, characterized by varying air movements over the Bellingshausen and Weddell Seas. This pattern facilitated an "atmospheric river," a flow of warm and moist air from lower latitudes, including continental South America/Atlantic and the southeast Pacific, as reflected in the precipitation's water stable isotope composition. This event is indicative of a potential trend toward more frequent and severe occurrences, emphasizing the urgent need for comprehensive winter research in the Antarctic Peninsula to understand the broader implications of extreme weather events and climate change. Early July 2023 had extreme winter warmth with rainfall in the northern Antarctic Peninsula, favored by an atmospheric river In recent decades, strengthened winter pressure dipole has directed northerly warm and moist air, resulting in warm events in the region We highlight the need for expanded winter research in the Antarctic Peninsula to better understand climate change and extreme weather events
Keywords: atmospheric river; warm events; climate extremes; antarctica; rainfall; moisture transport